TRANSPARENCY AND ACCOUNTABILITY AS DETERMINANTS IN THE FINANCIAL MANAGEMENT OF UNIVERSITIES: A STUDY ON STATE UNIVERSITIES IN MALANG CITY - Natawibawa, I Wayan Yeremia; Mulya, I Made Oka; Yoh, Wahyo Hendarto (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2019)
Educational organizations are public sector organizations, making transparency and accountability two important principles that must be reflected in their financial management. This requirement is enshrined in the Law of the Republic of Indonesia Number 12 of 2012 on University. Two factors that can potentially influence transparency and accountability of financial management are the presentation of financial report of the organization in question and accessibility to such statements. This research is intend to analyze the impact of financial report presentation and accessibility to financial reports on transparency and accountability of financial management of a state university in Malang City. Rate of returned and completed questionnaire is 100%, comprising of 252 questionnaires. Data analysis is conducted using multiple linear regression. There are two independent variables used in this research, namely the presentation of financial reports and accessibility to financial reports, and two independent variables, namely transparency and accountability of financial management. The result of this research indicates that the presentation of financial reports and accessibility to financial reports have a positive impact on transparency and accessibility in financial management. This in turn implies that the public would consider that financial management at the state university is accountable if its financial report is prepared in accordance with the applicable standards and easily accessed.